A sexually dimorphic pre-stressed translational signature in CA3 pyramidal neurons of BDNF Val66Met mice - Jordan Marrocco (Nature Portfolio, 2017)
Animals’ response to acute stress is known to be influenced by sex and genetics. Here the authors performed RNA-seq on actively translated mRNAs in hippocampal CA3 neurons in mice, and document the effects of sex and genotype (i.e., BDNF Val66Met) on acute stress-induced gene expression.